2011
DOI: 10.1007/s10811-011-9706-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen concentration on the growth of Nannochloropsis sp. at low light intensity

Abstract: In large-scale microalgal production in tubular photobioreactors, the build-up of O2 along the tubes is one of the major bottlenecks to obtain high productivities. Oxygen inhibits the growth, since it competes with carbon dioxide for the Rubisco enzyme involved in the CO2 fixation to generate biomass. The effect of oxygen on growth of Nannochloropsis sp. was experimentally determined in a fully controlled flat-panel photobioreactor operated in turbidostat mode using an incident photon flux density of 100 μmol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 25 publications
2
35
0
1
Order By: Relevance
“…Although this issue is not commonly addressed in small-scale cultivation because the used gas transfer apparatuses enable to provide sufficient air/CO 2 supply to promptly remove the DO out of the culture environment, it does seriously hinder the microalgal growth in many large-scale/industrial culture systems [7,8]. It has been demonstrated that the accumulated DO may cause damage to the photosynthetic apparatus, membrane or components of microalgal cells, thereby leading to diminished cell growth rate and/or collapse of cultivation [9][10][11]. In fact, photosynthesis in many microalgae species is tremendously inhibited when the DO concentration is over the level at air saturation (i.e., 0.225 mM at 20 • C) [12,13], even though the concentration of CO 2 is maintained at elevated levels [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although this issue is not commonly addressed in small-scale cultivation because the used gas transfer apparatuses enable to provide sufficient air/CO 2 supply to promptly remove the DO out of the culture environment, it does seriously hinder the microalgal growth in many large-scale/industrial culture systems [7,8]. It has been demonstrated that the accumulated DO may cause damage to the photosynthetic apparatus, membrane or components of microalgal cells, thereby leading to diminished cell growth rate and/or collapse of cultivation [9][10][11]. In fact, photosynthesis in many microalgae species is tremendously inhibited when the DO concentration is over the level at air saturation (i.e., 0.225 mM at 20 • C) [12,13], even though the concentration of CO 2 is maintained at elevated levels [13].…”
Section: Introductionmentioning
confidence: 99%
“…Over time, oxygen generated by photosynthesis will build up in the tubular part of the photobioreactor and quickly reach supersaturation concentration until the culture medium is circulated to the degassing chamber. The dissolved oxygen level accumulated throughout the long tube could cause damage to the photosynthetic apparatus, membrane structure, and cellular components of microalgal cells, thereby leading to reduced cell growth rate or collapse of culture . While oxygen accumulation is not a substantial complication in small‐scale culture devices, probably owing to sufficient power provided by the gas transfer systems to remove the accumulated oxygen or the tube length of the reactor being short enough that the degree of dissolved oxygen build‐up can be minimized, scale up to industrial systems exacerbates the issue of dissolved oxygen accumulation, which leads to failure of microalgal cultures .…”
Section: Introductionmentioning
confidence: 99%
“…Still, potential variation in log 10 IC50 due to, for example, differences in algal species and physiological state mean that inhibition parameters should be calibrated for each species. For example, a study by Raso et al (), which independently measured algal activity against DO concentration showed oxygen inhibition at lower dissolved oxygen concentrations (∼8 mg L −1 ) for Nannochloropsis sp. algae in a tubular photobioreactor.…”
Section: Resultsmentioning
confidence: 99%